'Do our lives matter?' Music, poetry, and Freedom School. (November 2018) - Shimshon-Santo, Amy
This article presents synergies between arts education, political consciousness raising, and leadership development for youth, and suggests roles for the arts in community organizing for personal and social change. Arts education is seen as a strategy to unleash creativity, affirm cultural assets, cultivate multiple literacies, critique oppressive social practices, and ignite freedoms. Rooted in the US civil rights movement of the 1960s, Freedom Schools became a national network committed to youth development. The case study, set in the Freedom School of South Los Angeles, introduces readers to geographical, cultural, and institutional contexts for the work; outlines a critical methodology for participatory action research; and shares transformational autoethnographies of teaching and learning in arts education classrooms. It is grounded in intersectional feminist methodologies, and is aimed at educators, artists, urbanists, and cultural studies practitioners. The work invested in youth voice and professional development of novice teachers by activating creativity and intergenerational mentorship to reimagine alternative futures. Short term project outcomes are conveyed, alongside longer-term implications for systemic change that values the lives of black and brown youth, families, and communities.